Pharmaceutical interventions from paediatric pharmacists. Issue 6 (1st February 2011) - Law, A; Lo, A; Stephenson, E
Abstract : Objective: The role of a clinical pharmacist is often seen simply as the supplier of prescribed medicines and their clinical and pharmaceutical knowledge is seldom recognised. Prescribing errors are common1 and feedback of errors improves both patient safety and future prescribing and raises standards in patient care. This study sets out to record clinical interventions made by pharmacists on the neonatal and paediatric wards and identify common daily problems and errors encountered over 6 months with the view of reducing patient harm. Methods: Each pharmacist was asked to record every occasion they intervened in clinical issues during their visits to wards. Interventions were documented on printed forms containing patient initials, consultant and categories adapted from the Pharmaceutical Care Network Europe Classification for Drug-Related Problems.2 Categories included type of problem (adverse reaction, drug choice problem, dosing problem, drug use problem, interactions and other), cause (drug selection, dose selection, drug use process, information, pharmacy logistics, patient issues and others), significance (minor – small improvement of patient care, moderate – significant improvement in patient outcome and major – life saving/prevents patient morbidity), prescription type (in-patient or discharge TTA) and eventual outcome (totally solved, partially solved, not solved and outcome unknown). Data have been collected from January 2009 and ongoing but for the purposes of this study, up to and including June 2009. Results: 315 interventions were recorded over the 6-month period by five or six pharmacists per month depending on rotational numbers. 170 (54%) were problems associated with dosing, followed by 89 (28%) as problems with drug choice. Within dosing problems, 28% of 170 were wrongly indicated, 22% were dosed incorrectly for weight and 20% for age. 56% of 89 drug choice errors were caused by drug history reconciliations and 19% for missing transcription. 54% of interventions were deemed moderate in severity with 43% classed as minor and 3% as major errors (and reported as an incident as per Trust guidelines). Most interventions (89%) were completely solved with the remainder being partially solved or the outcome was unknown; only two incidences were not solved by the pharmacist's intervention. 84% of problems occurred on inpatient drug charts, the remainder on discharge TTA. Numbers of interventions were not consistent over 6 months from 20 in 1 month to 85, and the total number of interventions reported per person varied from 114 to 25. Conclusion: Pharmacists intervene regularly on problems especially with dosing and drug choice. Most problems are moderate in nature and the majority of errors are found during inpatient stay and subsequently solved before discharge. Previous studies show a 4% incidence of reported errors1 ; we found an incidence of 6% with an average of 900 children seen by doctors per month, although not all children (accident and emergency) were admitted and seen by a pharmacist. Also note that the study did not start until midway through January. The number of actual interventions may also be higher than that reported in this study due to underreporting by ward pharmacists.3